MASALAH PENYAKIT MULU DAN PENANGGULANGANNYA DALAM PELAYANAN GERIATRIK TERPADU - Siti Sumariyah (Faculty of Dentistry, Universitas Indonesia, 2015)
Changes in the oral mucosa frequently is associated with aging. The epithelium becoming thinner, less hydrated and thus supposedly more susceptible to injury. Aging is characterized by decline in the ability of individuals to adapt to environmental stress. The major problems that affect mucous membranes in the aged include candidiasis, xerostomia, atrophic mucositis, aphthous stomatitis, herpes simplex, lichen planys, pemphigus vulgaris, and benign mucous membrane pemphigoif. A special disease of the oral mucosa with the greatest potential morbidity and mortality is cancer. The management of such oral mucosal diseases should be organized and developed to secure continuously adequate early detection, prevention and treatment of oral health problems. It requires the involvement and willingness of other health professionals, to get the optimal result.